Florida Carpenter Ants - R. J. Vazquez; Philip G. Koehler; Roberto M. Pereira; Jack Warner; Rudolf H. Scheffrahn (EDIS)
Carpenter ants are in the genus Camponotus, in which up to over 900 species have been described worldwide. They get their common name, “carpenter ant,” because some species excavate nests in wood. Carpenter ants are sometimes called bulldog ants or bull ants. However, not all species in the genus Camponotus are true carpenter ants because some nest in preformed cavities or in soil. This 5-page fact sheet was originally published as part of Pests in and around the Florida Home, and was written by R. J. Vazquez, P. G. Koehler, R. M. Pereira, J. Warner, and R. H. Scheffrahn, and published by the UF Department of Entomology and Nematology, October 2013.